2010
DOI: 10.1158/1078-0432.ccr-09-2123
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis C Virus Proteins Modulate MicroRNA Expression and Chemosensitivity in Malignant Hepatocytes

Abstract: Purpose: Hepatocellular cancer (HCC) is highly resistant to chemotherapy and is associated with poor prognosis. Chronic hepatitis C virus (HCV) infection is a major cause of HCC. However, the effect of viral proteins in mediating chemosensitivity in tumor cells is unknown. We postulated that HCV viral proteins could modulate therapeutic responses by altering host cell microRNA (miRNA) expression.Experimental Design: HepG2 malignant hepatocytes were stably transfected with full-length HCV genome (Hep-394) or an… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
86
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 112 publications
(89 citation statements)
references
References 48 publications
2
86
1
Order By: Relevance
“…38 Note that an earlier study showed that miR-193b targets Mcl-1 in malignant hepatocyte cells via the matched seed sequence that was essential for posttranscriptional repression. 39 Three scenarios could explain this discrepancy. First, the present study analyzes the interaction between miR-193b and the full length Mcl-1 3= UTR, whereas Braconi et al 39 examined a short fragment of the Mcl-1 3= UTR that included the seed pairing site.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…38 Note that an earlier study showed that miR-193b targets Mcl-1 in malignant hepatocyte cells via the matched seed sequence that was essential for posttranscriptional repression. 39 Three scenarios could explain this discrepancy. First, the present study analyzes the interaction between miR-193b and the full length Mcl-1 3= UTR, whereas Braconi et al 39 examined a short fragment of the Mcl-1 3= UTR that included the seed pairing site.…”
Section: Discussionmentioning
confidence: 99%
“…39 Three scenarios could explain this discrepancy. First, the present study analyzes the interaction between miR-193b and the full length Mcl-1 3= UTR, whereas Braconi et al 39 examined a short fragment of the Mcl-1 3= UTR that included the seed pairing site. Thus, the seedless miR-193b binding site in the Mcl-1 3= UTR could have been missing from the fragment studied by the Braconi group.…”
Section: Discussionmentioning
confidence: 99%
“…The expression of microRNA is also reported to be associated with HBV and HCV infections 52,53 which are closely related to HCC, and the association with hepatocarcinogenesis has been indicated. 54 Reduced expression of miR-122 in a chimpanzee model of HCV hepatitis/HCC was reported to result in successful control of HCC,55 and the clinical application to humans is greatly anticipated.…”
Section: Colorectal Cancermentioning
confidence: 99%
“…A growing body of evidence has demonstrated that miRNAs have played important roles in cancer development and clinical outcomes of cancer patients [11]. Up to date, different study cohorts find that miRNAs are involved in HCC development and some of them have been identified to correlate with prognosis or accepted to be potential therapeutic targets [12][13][14][15]. For example, the study by Jiang and his colleagues revealed that miR-199a, miR-21 and miR-301 were differentially expressed between tumor and adjacent benign liver.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, several deregulated miRNAs (e.g., miR-21, miR-101, miR-195, miR-122, miR-221, miR-223 and miR-224) have been shown to regulate cell growth, apoptosis, migration or invasion [17][18][19][20][21][22]. In conclusion, the ability of miRNAs to function as tumor promoters or suppressors in hepatocarcinogenesis has led to new insights into the molecular pathways involved in HCC [14,23]. To date, several oncogenes, caused by apoptosis-related molecules, such as T cell leukemia/lymphoma 1 (TCL1), myeloid cell leukemia sequence 1 (Mcl-1), cell division cycle 42 (CDC42) and phosphoinositide-3-kinase regulatory subunit 1 (PIK3R1), have been characterized as targets of the miR family [24][25][26][27][28][29].…”
Section: Introductionmentioning
confidence: 99%